New Insights in Genetic Cholestasis: From Molecular Mechanisms to Clinical Implications - Eva Sticova; Milan Jirsa; Joanna Pawłowska (Canadian Journal of Gastroenterology and Hepatology)
Cholestasis is characterised by impaired bile secretion and accumulation of bile salts in the organism. Hereditary cholestasis is a heterogeneous group of rare autosomal recessive liver disorders, which are characterised by intrahepatic cholestasis, pruritus, and jaundice and caused by defects in genes related to the secretion and transport of bile salts and lipids. Phenotypic manifestation is highly variable, ranging from progressive familial intrahepatic cholestasis (PFIC)—with onset in early infancy and progression to end-stage liver disease—to a milder intermittent mostly nonprogressive form known as benign recurrent intrahepatic cholestasis (BRIC). Cases have been reported of initially benign episodic cholestasis that subsequently transitions to a persistent progressive form of the disease. Therefore, BRIC and PFIC seem to represent two extremes of a continuous spectrum of phenotypes that comprise one disease. Thus far, five representatives of PFIC (named PFIC1-5) caused by pathogenic mutations present in both alleles of ATP8B1, ABCB11, ABCB4, TJP2, and NR1H4 have been described. In addition to familial intrahepatic cholestasis, partial defects in ATP8B1, ABCB11, and ABCB4 predispose patients to drug-induced cholestasis and intrahepatic cholestasis in pregnancy. This review summarises the current knowledge of the clinical manifestations, genetics, and molecular mechanisms of these diseases and briefly outlines the therapeutic options, both conservative and invasive, with an outlook for future personalised therapeutic strategies.